A history of cardiovascular magnetic resonance imaging in clinical practice and population science - Sanghvi, Mihir M.; Lima, João A. C.; Bluemke, David A.; Petersen, Steffen E. (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular magnetic resonance (CMR) imaging has become an invaluable clinical and research tool. Starting from the discovery of nuclear magnetic resonance, this article provides a brief overview of the key developments that have led to CMR as it is today, and how it became the modality of choice for large-scale population studies.